2020
DOI: 10.1186/s13287-020-01869-3
|View full text |Cite
|
Sign up to set email alerts
|

Reparative effect of mesenchymal stromal cells on endothelial cells after hypoxic and inflammatory injury

Abstract: Background: The renal endothelium is a prime target for ischemia-reperfusion injury (IRI) during donation and transplantation procedures. Mesenchymal stromal cells (MSC) have been shown to ameliorate kidney function after IRI. However, whether this involves repair of the endothelium is not clear. Therefore, our objective is to study potential regenerative effects of MSC on injured endothelial cells and to identify the molecular mechanisms involved. Methods: Human umbilical vein endothelial cells (HUVEC) were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…CB-ECFCs were incubated with increasing doses of TNFα. After 24 h, cells were analyzed for the expression of ICAM, VCAM and TIE-2 pro-inflammatory/injury markers [ 51 ]. We observed that 0.01 and 0.1 ng/ml of TNFα provided low inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…CB-ECFCs were incubated with increasing doses of TNFα. After 24 h, cells were analyzed for the expression of ICAM, VCAM and TIE-2 pro-inflammatory/injury markers [ 51 ]. We observed that 0.01 and 0.1 ng/ml of TNFα provided low inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Here, our results showed that compared with NS, HA, and PRP solution, IPFP-MSCs suspended in TE solution had strong adhesion at early stages. Previous studies normally analyzed number of adherent cells, with no further analysis of the adhesion morphology of MSCs [ 51 , 52 ]. In this study, adhesion area and height of IPFP-MSCs at 2 h were detected by SEM and Pro-film 3D scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Our manuscript focuses on readout of the TNFa, sTNF-R1/ R2, AP1/cFOS, and VEGF signaling axis in the context of detrimental effects of uremia on microvascular ECs and amelioration thereof by employing novel dialysis filters with improved molecular cutoff. For better understanding to readers, we have focused on these main mediators, but in principle the list of studied markers could be expanded to many other markers indicative of endothelial maladaptation/injury/damage markers, such as endothelial E-Selectin (ELAM-1), ICAM-1, VCAM-1, IL-6, IL-8, Tie-2 and the production of reactive oxygen species (ROS), as outlines in other studies on endothelial inflammation (37,46,(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%